Prostaglandin receptors EP and FP are regulated by estradiol and progesterone in the uterus of ovariectomized rats - Blesson Chellakkan S; Büttner Edgar; Masironi Britt; Sahlin Lena (BMC, 2012)
Abstract Background Prostaglandins are important for female reproduction. Prostaglandin-E2 acts via four different receptor subtypes, EP1, EP2, EP3 and EP4 whereas prostaglandin-F2alpha acts through FP. The functions of prostaglandins depend on the expression of their receptors in different uterine cell types. Our aim was to investigate the expression of EPs and FP in rat uterus and to identify the regulation by estradiol, progesterone and estrogen receptor (ER) selective agonists. Methods We performed four different rat experiments involving treatments with estradiol, progesterone and ER agonists. Real-time PCR and immunohistochemistry were employed to evaluate receptor expression. Results Our results showed that all mRNAs and proteins of EPs and FP are expressed in the rat uterus. The expression pattern and intensity of immunostaining vary between different cell types and treatments. The mRNA expression of all EPs and FP are downregulated by estradiol and the ERalpha specific agonist PPT, whereas the ERbeta specific agonist DPN downregulates only EP2 and EP4. The protein expression however, showed an increase in EP2 and EP3 after estradiol treatment. When treated with estradiol and progesterone in combination, the expressions of EP1 and EP3 are upregulated. Conclusions Regulation of EPs and FP expression by estradiol appears to be mainly modulated via ERalpha for EP1, EP3 and FP, while EP2 and EP4 also are affected by the ERbeta selective ligand. Our immunohistochemical data shows a cell specific regulation of prostaglandin receptors under the influence of ovarian steroids, where EP2 is estrogen regulated in all uterine tissues examined. EP1 and EP3 are upregulated by the combination of estradiol and progesterone. Thus, our observations indicate that estradiol and progesterone regulate the mRNA and protein expression of EPs and FP in a receptor and tissue specific way.